Lithuania’s economic trajectory in the shadow of the Ukraine conflict - Kseniia Kizilova (Mokslas: Lietuvos Ateitis)
The ongoing situation between Russia and Ukraine has sent shockwaves through Europe, impacting the economies of nearby nations like Lithuania. Lithuania, a member of the European Union, finds itself in a complicated position due to its historical and political connections to Russia and Ukraine. Using such methodology as literature review, correlation, and regression analysis, structural equation modelling this research dives into how war is affecting Lithuania’s economy, including changes in trade, energy security, and relocation of investments. Because of the sanctions against Russia, an important trading partner for Lithuania, their usual trade routes have been thrown off. This has forced Lithuania to look for new markets and other places to get energy. At the same time, Lithuania has had to spend more on its military and faces greater uncertainty because of the conflict, which has changed fiscal policies and investor confidence. The conflict has also sped up Lithuania’s move towards Western markets and strengthened its employment market. This paper takes a deep dive into Lithuania’s economic journey within the changing landscape of security, economic indicators, and policy reactions. The results emphasize both the weaknesses and strengths of Lithuania’s economy in the face of ongoing geopolitical conflict.